On the type Ia supernovae 2007on and 2011iv: evidence for Chandrasekhar-mass explosions at the faint end of the luminosity–width relationship. Issue 1 (14th March 2018) - Ashall, C; Mazzali, P A; Stritzinger, M D; Hoeflich, P; Burns, C R; Gall, C; Hsiao, E Y; Phillips, M M; Morrell, N; Foley, Ryan J
Abstract: Radiative transfer models of two transitional type Ia supernovae (SNe Ia) have been produced using the abundance stratification technique. These two objects – designated SN 2007on and SN 2011iv – both exploded in the same galaxy, NGC 1404, which allows for a direct comparison. SN 2007on synthesized 0.25 $\rm M_{{\odot}}$ of 56 Ni and was less luminous than SN 2011iv, which produced 0.31 $\rm M_{{\odot}}$ of 56 Ni. SN 2007on had a lower central density (ρc ) and higher explosion energy ( E kin ∼1.3 ± 0.3 × 10 51 erg) than SN 2011iv, and it produced less nuclear statistical equilibrium (NSE) elements (0.06 $\rm M_{{\odot}}$ ). Whereas, SN 2011iv had a larger ρc, which increased the electron capture rate in the lowest velocity regions, and produced 0.35 $\rm M_{{\odot}}$ of stable NSE elements. SN 2011iv had an explosion energy of ∼ E kin ∼0.9 ± 0.2 × 10 51 erg. Both objects had an ejecta mass consistent with the Chandrasekhar mass (Ch-mass), and their observational properties are well described by predictions from delayed-detonation explosion models. Within this framework, comparison to the sub-luminous SN 1986G indicates SN 2011iv and SN 1986G have different transition densities (ρtr ) but similar ρc . Whereas SN 1986G and SN 2007on had a similar ρtr but different ρc . Finally, we examine the colour–stretch parameter sBV versus L max relation and determine that the bulk of SNe Ia (including the sub-luminous ones) are consistent with Ch-mass delayed-detonation explosions, where the main parameter driving the diversity is ρtr . We also find ρc to be driving the second-order scatter observed at the faint end of the luminosity–width relationship.